Correspondencias y una aplicaci on a la teor ia de la producci on - Lezcano Chiclayo, Santos Raúl (2014)
This work is an application of some aspects of the correspondences theory and one of its applications to economic production theory when there exist is a range of inputs available; its subject is de ne so called \production correspondences", explore their proprieties and also give the economic and geometric interpretations of the properties of the imput and output correspondences.